Trends in corrections : interviews with corrections leaders around the world . - Hurley, Martha Henderson; Das, Dilip K., 1941- (CRC Press, 2015)
The first volume of the Trends in Corrections: Interviews with Corrections Leaders Around the World series introduced readers to the great diversity that exists cross-culturally in the political, social, and economic context of the correctional system. Presenting transcribed interviews of corrections leaders, it offered a comprehensive survey of correctional programming and management styles used across nations. The general conclusion drawn from the inaugural publication was that the correctional leaders interviewed exhibited striking similarities despite vast differences in the social and pol.